Modifying non-coding regions of linear DNA vaccines to explore the interplay of expression and inflammation in immunogenicity - David C. Stirling; Maria de Miguel Ferrer; Sungwon Kim; Madina Wane; Daniel Kysh; Lisa J. Caproni; John S. Tregoning (Human Vaccines & Immunotherapeutics)
The COVID-19 pandemic highlighted the need for rapidly deployable, flexible vaccine platforms; particularly RNA which is now being explored for several other pathogens. DNA vaccines have potential advantages over RNA, including cost of manufacture, ease of storage and potentially lower reactogenicity. However, they have historically underperformed in large animals and human trials due to low immunogenicity. The interplay between antigen expression and the innate immune response impacts the overall immune response to DNA vaccines. Here, we explore the effect of altering non-coding 5’ regions, on the immunogenicity of a closed linear DNA platform, Doggybone™ DNA (dbDNATM), produced by a rapid and scalable cell-free method. Using a mouse model, we found that enhancer sequences and DNA targeting sequences (DTS) increased influenza virus hemagglutinin (HA) expression and improved immune responses. Additional CpG motifs did not provide any immune benefit. We also found that the effect of non-coding sequences was target specific, with differing effects in influenza HA, SARS-CoV-2 Spike and eGFP constructs. To separate the effects of immune sensing of the DNA construct and the expression of the encoded antigen, we combined a separate CpG oligodeoxynucleotide (ODN) with the highest expressing DNA vaccine; we observed reduced expression, but higher inflammation resulting in equivalent immunogenicity. Further refinement is required to fully understand the interplay of factors required for the induction of protective immunity by DNA vaccines.